Acquired Resistance to BET-PROTACs (Proteolysis-Targeting Chimeras) Caused by Genomic Alterations in Core Components of E3 Ligase Complexes - Zhang, Lu; Riley-Gillis, Bridget; Vijay, Priyanka; Shen, Yu (Molecular cancer therapeutics, 2019)
Proteolysis-targeting chimeras (PROTAC) are bifunctional molecules that hijack endogenous E3 ubiquitin ligases to induce ubiquitination and subsequent degradation of protein of interest. Recently, it has been shown that PROTACs with robust and activities and, in some cases, drug-like pharmaceutical properties can be generated using small-molecule ligands for the E3 ligases VHL and CRBN. These findings stoked tremendous enthusiasm on using PROTACs for therapeutics development. Innate and acquired drug resistance often underlies therapeutic failures, particularly for cancer therapy. With the PROTAC technology progressing rapidly toward therapeutic applications, it would be important to understand whether and how resistance to these novel agents may emerge. Using BET-PROTACs as a model system, we demonstrate that resistance to both VHL- and CRBN-based PROTACs can occur in cancer cells following chronic treatment. However, unlike what was often observed for many targeted therapeutics, resistance to BET-PROTACs did not result from secondary mutations that affect compound binding to the target. In contrast, acquired resistance to both VHL- and CRBN-based BET-PROTACs was primarily caused by genomic alterations that compromise core components of the relevant E3 ligase complexes.